THE EFFECT OF MAGGOT FLOUR (Hermetia Illucens) FROM LAYING CHICKEN MANUFACTURES AS A SUBSTITUTION FOR FISH MEAL IN THE ration ON QUAIL EGG PRODUCTION - Dini Julia Sari Siregar; Warisman Warisman (Bajang Institute, 2023)
This research aims to determine the effect of giving maggot meal (hermetia illucent) from laying hen droppings as a substitute for fish meal in the ration on the production of quail (cortunix-cortunix japonica) eggs. The research design used was a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments studied were as follows: P0 = ration containing 12% fish meal, P1 = ration containing 9% fish meal + 3% maggot meal, P2 = ration containing 6% fish meal + 6% maggot meal, P3 = ration containing 3% fish meal + 9% maggot flour, P4 = Ration contains 12% maggot flour. The research results obtained are the highest feed consumption was in treatment P0 at 19.40 grams/head/day which was very significantly different from the feed consumption in treatment P1 at 18.58 grams/head/day, P2 at 17.30 grams/head/day, P3 at 16 .60 grams/head/day, and the lowest feed consumption was in treatment P4 at 14.57 grams/head/day. The best ration conversion was found in treatment P2 with a ration conversion value of 2.04 which was not significantly different from treatment P3 of 2.18, P1 of 2.26, P0 of 2.53, and P4 of 2.56. The highest egg production was in treatment P0 at 85% and P2 at 84.25% which was very significantly different from the lowest egg production in treatment P4 with egg production at 64%. The highest egg weight was found in treatment P1 at 10.63 grams/piece, which was not significantly different from treatment P0 at 10.20 grams/piece, P2 at 10.19 grams/piece, P4 at 10 grams/piece, and treatment P3 at 9 .80 grams/item. The highest egg mass was found in treatment P0 at 8.68 grams and P2 at 8.53 grams, which was not significantly different from the egg mass in treatment P3 at 7.79 grams, P1 at 7.75 grams, and P4 at 6.23 grams.